A clinical and radiological study of biodegradable subacromial spacer in the treatment of massive irreparable rotator cuff tears - Ricci, Matteo; Vecchini, Eugenio; Bonfante, Elia; Micheloni, Gian Mario; Berti, Mattia; Schenal, Giacomo; Zanetti, Gabriele; Sambugaro, Elena; Maluta, Tommaso; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2017)
Purpose: The aim of this retrospective study was to report the clinical and radiographic results of the biodegradable subacromial spacer (InSpace Balloon®) implantation in patients with massive irreparable rotator cuff tears. Materials and methods: From February 2014 to October 2015, 30 patients affected by massive irreparable rotator cuff tears were treated with the implantation of InSpace Balloon®. Clinical evaluation (Constant Score and VAS), X-rays and MR imaging were performed preoperatively in all patients and 3, 6, 12 and 24 months after surgery, dividing patients in different groups according to the time elapsed from surgery. Results: Constant Score increased from 39.89 to 62.33 points (p 0.0002) in the 6 months group and from 41.66 to 65.38 points (p< 0.0001) in the 12 months group. ROM (Range of Movement) and ADL (Activity of Daily Living) significantly improved with the contemporary reduction of VAS and pain at 12 months and, furthermore, an increase of functional performance with reduction of pain was registered at 24 months. Conclusions: Our results supported the surgical procedure of the arthroscopic implantation of biodegradable subacromial InSpace Balloon® for irreparable massive cuff tears in worker patients and with recreational activities’ demands in order to recover the shoulder function with a reduction of the pain.